Pengabdian Masyarakat Melalui Edukasi Pertanian Berbasis Studi Lapang Pada Subak Sembung Kota Denpasar - L P K Pratiwi; N P Sukanteri; I M Budiasa; I K Arnawa; N L G P Dewi; B Pasman (Institut Nalanda, 2023)
Subak Sembung is one of the urban agricultural ecotourism development areas. The main problem for target partners is that there is no identification of food crops, no public information in the implementation of Tri Hita Karana-based subak, and educational spaces that are not representative in field study-based edutourism. The service method is carried out through socialization, training, mentoring, monitoring and evaluation. The implementation of the community service program has been successful in increasing knowledge and skills in developing Subak's tourist attraction through field-based organic farming through tracking tourism package packaging and developing organic farming through the use of compost, liquid organic fertilizer, biopesticides and packaging of tour packages. Thus, through these community service activities, we are able to produce output that increases the income of farmers and local communities in the form of attractive educational tourism packages.